Development of AR-Based PPT Media in Science Subjects to Increase Learning Motivation of 6th Grade Elementary School Students - Nurlaela; Barokah, Awalina (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to explore the development of AR-based PowerPoint (PPT) media for teaching Natural Sciences (IPA), specifically the solar system topic, in sixth-grade elementary school. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation phases. The study was conducted at SDIT An-Nisa and involved 26 sixth-grade students as respondents. Data were collected through observation, interviews, and questionnaires. Validation sheets were used to assess the media's quality, evaluated by media experts, subject matter experts, and language experts. The effectiveness of the media was measured using the N-Gain score. The validation results indicated that the AR-based learning media was highly valid, with an average score percentage of 95.31%. In terms of effectiveness in enhancing students’ learning motivation, the media achieved a score of 84.75%, which is categorized as effective. Based on these findings, the AR-based PPT learning media can serve as an effective alternative tool for teaching Natural Sciences and can significantly improve the learning motivation of sixth-grade students.